Nostalgia bez pamięci. Spojrzenie na przestrzeń kulturową Warmii i Mazur - Maleszka, Michał (Studia Etnologiczne i Antropologiczne, 2012)
The article is an attempt to present ways of perceiving a post-German cultural space in Warmia and Mazuria. The very issue is dealt with from the point of view of existing historical, political and ethnic discontinuity as the main feature defining the modern nature of the region. Also, the succession of generations in post‑migration society typical of all regained lands described by Zdzisław Macha is used here. The text deals with the issue of a social imagination as the starting point in shaping the imagination of the past. The emphasis is put on the architecture, spacious order, popular iconographic representations of the past and post‑German symbolism. The role of nostalgia as a dominating way of perceiving what is gone is also elaborated on.